Ultra-sensitive H2+sensors based on flame-spray-made Pd-loaded SnO2+sensing films - C. Liewhiran (2018)
In this paper, ultra-sensitive hydrogen (H2+) gas sensors based on flame-spray-made Pd-catalyzed SnO2+nanoparticles is presented. Pd-loaded SnO2+crystalline nanoparticles with high specific surface area and well-controlled size were synthesized by flame spray pyrolysis (FSP) in one step. The particle properties were characterized by XRD, BET, SEM, TEM and EDS analyses. The H2+-sensing performances in terms of sensor response, response time and selectivity were optimized by varying Pd concentration between 0.2 and 2 wt%. An optimal Pd concentration for H2+sensing was found to be 0.2 wt%. The optimal sensing film (0.2 wt% Pd/SnO2+, 10μm in thickness) showed an ultra-high sensor response of ∼104to 1 vol% of H2+at 200°C and very short response time within a few seconds. Moreover, the optimum sensing temperature of Pd-loaded SnO2+films was shifted to a lower value compared with that of unloaded SnO2+film. The significant enhancement of H2+sensing performances was attributed to highly effective spillover mechanism of well-dispersed Pd catalyst in SnO2+matrix at low Pd-loading concentration. Furthermore, the catalyst selectivity of Pd toward H2+was found to be significantly higher than those of two other noble metals including Pt and Ru, respectively. Therefore, the flame-made 0.2 wt% Pd/SnO2+sensors is one of the most promising candidates for highly sensitive and selective detection of H2+. © 2012 Elsevier B.V. All rights reserved.